1995
DOI: 10.1139/z95-085
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and reproductive attributes of dispersers in two populations of the subterranean rodent Ctenomys talarum (tuco-tuco)

Abstract: The demographic and reproductive characteristics of dispersers in the fossorial rodent Ctenomys talarum, the tuco-tuco, were studied by removing animals from two experimental plots. Data on dispersers' attributes were compared with those of resident and transient individuals from previous capture–mark–release and removal studies performed in the same localities. Average weekly dispersal by tuco-tucos was 2.38% (range 0–5.75%) at Necochea and 5.75% (range 0–15.75%) at Mar de Cobo. The low proportion of disperse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 37 publications
1
34
0
2
Order By: Relevance
“…In fact, the optimal dispersal theory for subterranean rodents (Nevo 1979) predict that once adults have established their territories, they will remain sedentary through their lives. The analyzed animals in the present study, sexually active adults, differ from the typical dispersers identified for other subterranean rodents as mostly juveniles and subadults (Howard andChilds 1959, Williams andCameron 1984) or non-reproductive adults (Malizia et al 1995, Zenuto andBusch 1998).…”
Section: Discussionmentioning
confidence: 59%
“…In fact, the optimal dispersal theory for subterranean rodents (Nevo 1979) predict that once adults have established their territories, they will remain sedentary through their lives. The analyzed animals in the present study, sexually active adults, differ from the typical dispersers identified for other subterranean rodents as mostly juveniles and subadults (Howard andChilds 1959, Williams andCameron 1984) or non-reproductive adults (Malizia et al 1995, Zenuto andBusch 1998).…”
Section: Discussionmentioning
confidence: 59%
“…Based on the number of pregnant C. talarum during the breeding season, average number of litters year" female-1 is > 1. Except in June, sex ratios depart from 1:1, with an excess of females on the order of 1:1.63 (Malizia and Busch 1991;Malizia et al 1995).…”
Section: General Charactersmentioning
confidence: 93%
“…Females and males distribute themselves uniformly over an area. Sex ratios did not differ from 1:1 in transients and dispersers, whereas residents have an excess of females (Malizia et al 1995;Pearson et al 1968). Depth of burrows ranges between 10 and 35 cm (Contreras 1973).…”
Section: General Charactersmentioning
confidence: 96%
“…Los métodos alternativos que permiten obtener información respecto de interacciones sociales en roedores subterráneos solitarios incluyen el trampeo de extracción total y el de marcado y recaptura (Hansen & Millar 1959, Vaughan 1962, Patton & Feder 1981, Busch et al 1989, Daly & Patton 1990, Malizia et al 1995, Lacey et al 1998, Zenuto & Busch 1998). El aporte de la radiotelemetría permite conocer más detalles respecto de movimientos de los individuos (Bandoli 1987, Zuri & Terkel 1996, Lacey et al 1997, 1998) y su evolución en el tiempo (reconocer si son solitarios o sociales, la ubicación relativa de sexos en el terreno, quiénes se dispersan, los patrones temporales de actividad, los cambios en las afinidades espaciales entre individuos).…”
Section: Revista Chilena De Historia Naturalunclassified
“…Ambos sexos en todas las edades (excepto las crías hasta el destete) son sedentarios y presentan territorialidad individual (Busch et al 1989). Dos poblaciones de esta especie muestran diferencias en caracteres demográficos (Busch et al 1989, Malizia 1994, Malizia et al 1995, Malizia & Busch 1997. La población de Mar de Cobo se caracteriza por altas densidades (65 ind ha -1 ), proporciones sexuales desviadas hacia las hembras en adultos y dispersión con predominio de machos.…”
Section: Revista Chilena De Historia Naturalunclassified